The use of ethnobotanicals in the management of inflammation in Nigeria: a review - Fasola, TR; Iyamah, PC (International Journal of Environment, 2015)
Inflammation, one of the leading health issues in recent times call for concern. Many plants used in the management and treatment of inflammation in various parts of Nigeria have not been properly harnessed hence this review. The result of this review revealed that plants commonly used for the treatment of inflammation include: Zingiber officinale, Alstonia boonei, Plumbago zeylanica, Ocimum basilicum, Parquetina nigrescens, Peperomia pellucida, Abrus precatorius, Tetrapleura tetraptera, Alchornea cordifolia, Terminalia ivorensis, Aspilia africana, Ageratum conyzoides and Hymenocardia acida. Altogether 74 plant species are ethnobotanicals used in the management and treatment of inflammation. The plants were enumerated with their family names, common and local names, possible chemical constituents, part(s) used, route of administration and subsequent references where available. DOI: http://dx.doi.org/10.3126/ije.v4i2.12620 International Journal of Environment Vol.4(2) 2015: 1-18